The COVID-19 pandemic and entrepreneurship in Germany: First observations and interpretations - Michael Fritsch; Maria Greve; Michael Wyrwich (Friedrich Schiller University Jena, 2021)
The COVID-19 pandemic severely affected not only incumbent firms, but also the emergence of start-ups. This paper investigates and analyzes the pandemic's effect on new business formation, as well as business exits and insolvencies, in Germany. We find that the overall level of business registrations slightly decreased during the first year of the pandemic, but that the effect is specific to certain industries. Innovative manufacturing industries and technology-oriented services experienced an increase in numbers of start-ups. High subsidies and a temporary suspension of important criteria obliging firms to declare insolvency weakened market selection resulting in fewer exits in 2020. The relaxation of insolvency regulations may lead to considerable numbers of "zombie" firms. Generally, the pandemic re-enforced ongoing structural change, but also exerted specific effects that may be temporary in nature.
Keywords: L26; O52; I18; 330; COVID-19; entrepreneurship; new business formation; Germany